Emerging Powers in International Politics 2019
DOI: 10.4324/9781315197159-8
|View full text |Cite
|
Sign up to set email alerts
|

Compound soft power: the BRICS and the multilateralization of soft power

Abstract: This article offers a complementary analysis to the prevailing literature on soft power by addressing the issue of multilateral soft power. While the prevailing literature on soft power tends look at how soft power manifests itself within individual nations, this article attempts to analyze the manifestations of collective soft power in the vehicle of a multilateral organization. This can be referred to as compound soft power. Such an analysis looks at a macro-level class of soft power. In doing so, it looks m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…They argue that although conceptions of soft power in China are rooted in the cultural norms of traditional China, notions of soft power in the United States are rooted in contemporary cultural characteristics. The foundation of economic and development ideas are the primary pillars of China's soft power, whereas the United States places a greater focus on liberal political and civic principles (Gallarotti, 2016).…”
Section: Characteristics Of Chinese Soft Powermentioning
confidence: 99%
See 1 more Smart Citation
“…They argue that although conceptions of soft power in China are rooted in the cultural norms of traditional China, notions of soft power in the United States are rooted in contemporary cultural characteristics. The foundation of economic and development ideas are the primary pillars of China's soft power, whereas the United States places a greater focus on liberal political and civic principles (Gallarotti, 2016).…”
Section: Characteristics Of Chinese Soft Powermentioning
confidence: 99%
“…The economic dimension measures a country's power by measures such as calculating GDP, access to raw materials and energy sources such as oil, gas, coal, uranium, sufficient water, fertile land, advanced technology and industry, and other criteria. In a post-American book, Farid Zakaria states that it has now made China a unique set of factors: one of the world's largest, the fastest growing economy, the largest producer, the second consumer, the largest saver and the second cost Military builder (Erickson & Strange, 2015;Gallarotti, 2016). China's average annual economic growth rate of about 10 per cent has surprised the world; and, with China joining the WTO in 2001 and passing private property laws in 2007, the trend has continued.…”
Section: Economic Dimensionsmentioning
confidence: 99%
“…The instruments of soft power are adopted to create a positive image of the state, to propel it as an exemplary state, one that all other nations would want to be like or associate themselves with. “The attraction can be so strong that other nations may even attempt to emulate the policies and actions of Soft Power nations” (Gallarotti, , p. 7). These instruments affect almost all aspects of the state's social fabric in favor of the interests of the soft power nations, which is one of the reasons why the concept is challenged as being a form of cultural imperialism.…”
Section: Joseph Nye's Conception Of Soft Powermentioning
confidence: 99%
“…The available literature in Africa largely covers the application and enhancement of the concept of soft power based on Joseph Nye's conception of soft power. The prevailing literature tends to look at how soft power manifests itself within individual nations and how it is implemented (Gallarotti, ). A literature review of the different analyses of South Africa's soft power by Ogunnubi () showed three strands of soft power literature, namely “prescriptive, utilitarian and comparative” (2015, p. 40).…”
Section: Soft Power From An African Perspectivementioning
confidence: 99%